Performance evaluation of drilling tools during machining plain Carbon Fiber Reinforced Polymer (CFRP) - Konneh, Mohamed; Zaini, Mohamad Hamzi (Asian Research Publishing Network (ARPN), 2015)
The demand of CFRP have been arises because of their capabilities and high strength to weight ratio properties. It has been remarkably used in most field nowadays as an example in aerospace industries as it provide weight reduction and reduce the fuel consumption at the same time. However, the inherent anisotropy, inhomogeneous properties of CFRP and low bonding strength within the laminates make machining of these composite materials results in several undesirable effects such as delamination, burr and chipping. This experimental study was conducted on drilling CFRP using 3mm-diameter ball nose Diamond coated, Titanium Aluminum Nitride (TiAlN) coated and uncoated tool. Relationship between the machining variables and the output variables is analyze and the tool that performs better were selected so that the experiments can be continue to prove the findings. It was observed that minimal delamination at entry and exit is achieved when using TIAlN at high spindle speed and feed.